Public health palliative care interventions that enable communities to support people who are dying and their carers: a scoping review of studies that assess person-centered outcomes - Peeler, Anna; Doran, Alexandra; Winter-Dean, Lee; Ijaz, Mueed; Brittain, Molly; Hansford, Lorraine; Wyatt, Katrina; Sallnow, Libby; Harding, Richard (Frontiers in Public Health, 2023)
Background Public health palliative care views communities as an integral part of care delivery at the end of life. This community-provider partnership approach has the potential to improve end-of-life care for people who are dying and their carers. Objective To identify and appraise the current literature related to public health interventions that enable communities to support people who are dying and their carers. Methods A scoping review was conducted, applying Arksey and O'Malley's methods. Data was extracted and synthesized using narrative techniques, and results are reported using PRISMA guidelines. Results The search yielded 2,902 results. Eighteen met inclusion criteria and were included in the analysis. Interventions were categorized according to their target population: people with life-limiting illness (ex. facilitated social interaction, helplines and guided discussions about death and dying); carers (ex. social support mapping, psychoeducation, and community resource identification and facilitation); or dyads (ex. reminiscence activities, practical and emotional support from volunteers, online modules to bolster coping mechanisms). Public health palliative care approaches were delivered by key community stakeholders such as community health workers, volunteers, peer mentors, and pre-established support groups. Despite reported challenges in identifying appropriate tools to measure effectiveness, studies report improvement in quality of life, loneliness, social support, stress and self-efficacy. Conclusion We found that community-engaged palliative care interventions can lead to appreciable changes in various outcomes, though it was difficult to determine in which contexts this approach works best because of the dearth of contextual information reported. Based on the varied design and implementation strategies, it is clear that no one method for enhancing end of life care will benefit all communities and it is crucial to engage community members at all stages of the design and implementation process. Future research should be grounded in appropriate theory, describe contextual differences in these communities, and should specifically examine how demographics, resource availability, and social capital might impact the design, implementation, and results of public health palliative care interventions.